A Study of Eimeria Species in Sheep in Mosul City - M. H. Hasan; H. M. Abed (Iraqi Journal of Veterinary Sciences, 2012)
The study was conducted to diagnose and study species of Eimeria in sheep in Mosul city from beginning of September2009 to end May 2010, as well as to determine the percentage and intensity of infection of Eimeria species. Five hundredfecal samples of sheep with different ages were collected from different areas of the Mosul city. The results showed that totalpercentage of Emeria infection was 63.6%. The variations in percentage of infection were recorded according to month ofstudy. Highest percentage was recorded in March being 89.2% and the lowest in September 25.9%. The species E. ovinarecorded the highest infection rate 86.7%, while the species E. granulosa represented lowest infection rate 10%. Moreover theintensity of infection was higher in young ages and lower in adult. The results were detected that indoor sheep infection withhigh parasitic infection 69.9% whereas outdoor animals have an infection rate 25.3%. The morphological characters of oocystswere varied according to species of Eimeria has been studied. Fifty of intestinal and abomasal samples from both slaughteredin shops butchery in Mosul city and dead animals were examined to detect Eimeria infection, and results show that infectionpercentage was 56.4% in intestine of slaughtered animals and 36.3% in dead animal. Moreover no infection of Eimeria weredetected in abomasums in both slaughtered and dead animals. The oocysts of (E. parva, E.pallida and E. ovinoidalis) detectedat more than 5000 oocysts per gram of intestinal contents. The intestinal secraping stained with Giemsa stain reveals thepresence of different developmental stages of parasites in wall of intestine. The histopathological sections of intestine revealedthe different pathological changes concerning of Eimeria infection.